Project approach: the essence and features of application in public administration - Polikrovsky, Roman (Herald of Economics, 2024)
Introduction. The application of the project approach in the field of public administration is a fairly effective means of improving the main economic indicators of not only state but also regional development. Projects implemented by public authorities are important in the process of development of the national economic system and act as a fairly effective management tool. Implementation of projects activates the target orientation of the public management system; provides an absolute and permanent solution to various problems in the field of economy, ecology, social security, etc.; achieving the defined goal of social development in the country. Purpose of the research. Disclosure of the essence and features of the application of the project approach in the field of public administration. Research metods. In the process of writing this article, the following methods were used: analysis and synthesis, generalization method, comparative method and systematization method, system analysis method, logical and dialectical method. Results. The essence of the project approach in the field of public administration, which acts as a rather effective means of improving the main economic indicators of not only state, but also regional development, is revealed. The essence of the concept of «project» has been defined and it has been clarified that the project is a certain document that provides, through the use of special tools and methodology, the description, argumentation and detailing of certain activities in relation to the achievement of a predetermined and long-awaited goal together with a clearly defined resource base with a specific time frame . The essence of the concept of «project management» was revealed and it was established that «project management» is a short-term managerial and professional activity associated with planning, organization, stimulation and control over the appropriate use of all types of resource provision due to the application of a complex of special methodologies and tools in the process achievement of pre-defined goals within the defined project implementation period. The main features of the project approach in the field of public administration are given. Perspectives. Prospects for further research consist in substantiating the expediency of analyzing the effectiveness of implementing a project approach in managing the activities of local self-government bodies and territorial communities.